The Design and Research a New Kind Multistage Condensation Filtration Disengaging Gear - Wang Ying; Zhang Jiheng; Sun Ying; Wu Bangxi; Wang Qixiao; Zhao Quanhua (Zhileng xuebao)
The structure of automatic cascade refrigeration system is simple, and the operation is reliable. Since the non-azeotropic mixed refrigerants are used, whether the condensing separation is complete or not will directly affect the cooling efficiency. A new type of multistage condensing filtration disengaging gear is proposed in the paper. A test-bed of automatic cascade refrigeration system equipping with the device is set up for actual application research. The results show that the device can separate high and low boiling point group efficiently. Because of its simple structure and low cost, the device may have important potential of practical application.